Nurses' experiences and understanding of workplace violence in a trauma and emergency department in South Africa - Maureen Kennedy; Hester Julie (AOSIS, 2013)
Violence in South African society has reached epidemic levels and has permeated the walls of the workplace. The aim of the study was to gain a deeper understanding of how nurses experience and understand workplace violence perpetrated by patients, and to make recommendations to reduce this type of violence. A qualitative, exploratory and descriptive study was conducted to explore the experiences and coping mechanisms of nurses regarding workplace violence. The purposive sample comprised eight nurses working in the Trauma and Emergency Department in the Western Cape, South Africa. Thematic analysis was done of the semi-structured interviews. Four main themes and 10 categories were identified. Nurses are experiencing physical threats, verbal abuse and psychological and imminent violence on a regular basis. They tend to 'normalise' abusive patient behaviour because of the perception that workplace abuse 'comes with the territory', which resulted in under-reporting. However, perpetrators received compromised care by being avoided, ignored or given only minimal nursing care. Coping mechanisms ranged from using colleagues as sounding boards, helping out with duties, taking a smoke break and using friends and family to get it 'off their chest'. The tolerance of non-physical violence and the absence of policies to deal with the violence, contribute to under-reporting. Geweld in die Suid-Afrikaanse samelewing het epidemiese vlakke bereik en selfs werksplekke binnegedring. Die doel van die studie was om 'n dieper begrip te verkry van hoe verpleegsters geweld deur pasiënte by die ​​werksplek ervaar en verstaan, en aanbevelings te maak om hierdie tipe van geweld te verminder. 'n Kwalititatiewe, eksploratiewe en beskrywende ontwerp is gebruik om die ervaringe en hanteringsmeganismes te verken van verpleegkundiges wat aan werkpleksgeweld blootgestel was. 'n Doelgerigte steekproef is gedoen bestaande uit agt verpleegkundiges werksaam in die Trauma en Nooddienste Departement in die Weskaap, Suid Afrika. Die semi-gestruktureerde onderhoude is kwalitatief ontleed vir temas. Vier hooftemas en 10 kategorieë is geïdentifiseer. Verpleegkundiges ervaar dreigemente van fisiese geweld, verbale misbruik en psigiese en dreigende geweld gereeld. Hulle is geneig om pasiënte se misbruikende gedrag te 'normaliseer' omdat hulle die persepsie het dat geweld of misbruik 'deel van die werksomgewing' is. Hierdie persepsie gee aanleiding tot onder-rapportering van nie-fisiese geweld en gekompromitteerde sorg deurdat skuldige pasiënte of vermy, geïgnoreer of minimale sorg gegee word. Hanterings meganismes sluit in reflektering teenoor kollegas, uithelp met take, die gebruikmaking van 'n rook breek, en ontlaaing teenoor familielede en vriende. Die toleransie van nie-fisiese geweld en die gebrek van beleidsriglyne dra by tot die onder-rapportering van werksplek geweld.